Policy strategies for vehicle electrification - Gunnar Lindberg; Lasse Fridstrøm (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2015)
An increase in the market share of electric vehicles is one possible policy strategy for greenhouse gas (GHG) abatement. Many governments have introduced schemes to increase the market uptake - fiscal incentives, subsidies and various regulatory policies such as support for charging stations, free parking facilities or access to restricted road lanes as well as R&D funding. A number of partial studies do exist, but the comprehensive comparative study on the effect of these different incentives has yet to be done. Based on the experience until today it is, however, possible to explore the policy options.
Keywords: 330; Elektrofahrzeug; Nachhaltige Mobilität; Förderung erneuerbarer Energien; Norwegen; OECD-Staaten